Cultural Adaptation of Evidence-Based Lifestyle Interventions for African American Men With Prostate Cancer: A Dyadic Approach. Issue 6 (November 2020) - Cho, Dalnim; Basen-Engquist, Karen; Acquati, Chiara; Pettaway, Curtis; Ma, Hilary; Markofski, Melissa; Li, Yisheng; Canfield, Steven E.; Gregg, Justin; McNeill, Lorna H.
Although a number of lifestyle interventions have been developed for cancer survivors, the extent to which they are effective for African American men with cancer is unclear. Given that African American men have the highest prostate cancer burden and the lack of proven interventions, this study developed a culturally-tailored lifestyle intervention for African American men with prostate cancer and their partners that aimed to improve healthy lifestyle behaviors (physical activity and healthy eating) and quality of life. The aim of the present study is to provide a detailed overview of the model-based process of intervention adaptation. Based on the IM Adapt approach (Highfield et al., 2015) and Typology of Adaptation (Davidson et al., 2013), the present study adapted existing, evidence-based interventions to address African American prostate cancer survivors' and their partners' potential unmet needs including anxiety/uncertainty about cancer progression, communication between partners, cultural sensitivity, and concordance/discordance of motivation and behaviors between partners. The intervention adaptation was a comprehensive and fluid process. To the best knowledge of the author, this is the first couple-based lifestyle intervention specifically developed for African American men with prostate cancer. The present study will be highly informative to future investigators by providing flexible and detailed information regarding lifestyle intervention adaptation for racial/ethnic minority men with prostate cancer and their partners.